Clinical, endoscopic and cytologic evaluation of airways of horses pulling (Revista Sistemas de Producción Agroecológicos, 2015)
Disorders of the respiratory system have a key role in reducing the athletic performance of horses, tests such as bronchoscopy that is performed with flexible endoscope, and cytological (tracheal washings) have been used as diagnostic methods in animals with symptoms of respiratory failure. In recent years its implementation has had a significant increase due to its effectiveness in the opinions, resulting in decreased treatment time and costs. In this study, samples were taken to ten horses without defined breed, aged between 7 and 15 years, from clinical large animal veterinary hospital of the Federal University of Rio Grande do Sul (UFRGS), which nine were used for pulling in the metropolitan area and one for horse racing in Porto Alegre. All animals underwent clinical examination, emphasizing airway four endoscopies were performed and ten samples of tracheal secretions were collected by washing and percutaneous aspiration. The washed cell suspension was centrifuged for extended on slides, which were stained by the method of panoptical fast (differential staining), which allows the observation of blood cells. Descriptive statistics of the variables analyzed was performed. The animals showed heart rate 39.2 ± 1.44 beats per minute (bpm), respiratory rate 19.7 ± 2.37 breaths per minute (rpm), temperature 38.25 ± 0.08°C, hematocrit 34.7 ± 1.09%, erythrocyte count 7.25 ± 0.27 x 106/ml, hemoglobin 11.34 ± 0.042 g/dl, mean corpuscular volume average 49.85 ± 0.96 fentoliters (fl), 32 corpuscular hemoglobin concentration 77 ± 0.45 g/dl, platelets 183.8 ± 10.98 x 103/ml, total plasma proteins 7.3 ± 0.13 g/dl, total leukocytes 9,880 ± 470/ml, neutrophils 5,910 ± 560/ml, eosinophils 359.2 ± 70.8/ml, lymphocytes 3,420 ± 420/ml and monocytes 339.8 ± 50.12/ml. In tracheal wash cytology were determined the percentages of epithelial cells in 42.3 ± 9.35, lymphocytes 3.3 ± 1.13, macrophages 20.1 ± 5.35, neutrophils 26.4 ± 8.37 and eosinophils 2.7 ± 1.78. Finally the results of endoscopic examination in horses were: 1) normal amount of mucus and absence of bacteria (healthy), 2) increased production of mucus and bacteria in the extracellular medium and squamous cell surface, 3) cellular degeneration and picnosis, 4) phagocytes and cell debris, and 5) fungus in the extracellular background and phagocytosis, observed Hematoidin crystals and apoptotic processes. It is concluded that endoscopy and tracheal wash cytology are essential tools for the diagnosis of respiratory diseases, allowing the identification of functional disorders, glimpsing the predominant cell type, which causes the existing inflammatory process.
Keywords: bronchoscopy; respiratory system; transtracheal wash